ED50 of ciprofol combined with different doses of remifentanil during upper gastrointestinal endoscopy in school-aged children: a prospective dose-finding study using an up-and-down sequential allocation method - Zhang, Xu; Zhang, Ning; Song, Haicheng; Ren, Yueyi (Frontiers in Pharmacology, 2024)
Objective: This study aimed to determine the 50% effective dose (ED50) of ciprofol when combined with different doses of remifentanil for upper gastrointestinal endoscopy in school-aged children and to evaluate its safety. Methods: This study involved school-aged children who were scheduled to undergo upper gastrointestinal endoscopy under deep sedation. The children were randomly assigned to two groups: remifentanil 0.3 µg/kg (R0.3) and remifentanil 0.5 µg/kg (R0.5). Anesthesia was induced using remifentanil, followed by ciprofol. The dose of ciprofol for each patient was determined by Dixon up-down sequential method. If the MOAA/S score was ≤1 and the child did not exhibit significant movement or coughing during the endoscopy process, sedation was considered successful. The first patient in each group received 0.5 mg/kg ciprofol. The dose of ciprofol was adjusted by 0.05 mg/kg based on the response of the previous patient. The primary outcome was the ED50 of the ciprofol-induction dose. The total ciprofol doses, onset times, awakening times, and adverse reactions were recorded. Results: 1) The Dixon method was used to collect crossovers data from each group, and the ED50 values of the R0.3 and R0.5 groups were calculated to be 0.390 mg/kg (95% CI 0.356--0.424 mg/kg) and 0.332 mg/kg (95% CI 0.291-0.374 mg/kg), respectively. The ED50 of ciprofol in the R0.3 group was significantly higher than that in the R0.5 group (p < 0.05). 2) The onset time and recovery time of the R0.5 group were shorter than those of the R0.3 group (p < 0.05). When the two groups were compared, the total dose of ciprofol in the R0.5 group decreased (p < 0.05). 3) Compared with the R0.3 group, the incidence of respiratory depression during induction in the R0.5 group increased (p < 0.05). Conclusion: This study explored the ED50 of ciprofol combined with different doses of remifentanil for successful sedation in upper gastrointestinal examinations in school-aged children. Compared to the use of remifentanil 0.3 µg/kg, the combination of ciprofol with remifentanil 0.5 µg/kg significantly reduced the ED50 required to prevent body movement or cough during endoscope insertion but increased the incidence of respiratory depression.